1999
DOI: 10.1172/jci5574
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of platelet-activating factor acetylhydrolase is a severity factor for asthma

Abstract: Asthma, a family of airway disorders characterized by airway inflammation, has an increasing incidence worldwide. Platelet-activating factor (PAF) may play a role in the pathophysiology of asthma. Its proinflammatory actions are antagonized by PAF acetylhydrolase. A missense mutation (V279F) in the PAF acetylhydrolase gene results in the complete loss of activity, which occurs in 4% of the Japanese population. We asked if PAF acetylhydrolase deficiency correlates with the incidence and severity of asthma in Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
84
2
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(98 citation statements)
references
References 50 publications
9
84
2
3
Order By: Relevance
“…These suppressive effects of plasma PAF-AH are thought to be due to its ability to hydrolyze PAF and PAF-like oxidized phospholipids. Four percent of the Japanese population lack plasma PAF-AH, and such a deficiency or decrease in plasma PAF-AH activity may be associated with severe asthma (31)(32)(33), atopy (32), stroke, and various cardiovascular diseases (34 -37). Intracellular type II PAF-AH (PAF-AH (II)) is a monomeric 40-kDa enzyme.…”
mentioning
confidence: 99%
“…These suppressive effects of plasma PAF-AH are thought to be due to its ability to hydrolyze PAF and PAF-like oxidized phospholipids. Four percent of the Japanese population lack plasma PAF-AH, and such a deficiency or decrease in plasma PAF-AH activity may be associated with severe asthma (31)(32)(33), atopy (32), stroke, and various cardiovascular diseases (34 -37). Intracellular type II PAF-AH (PAF-AH (II)) is a monomeric 40-kDa enzyme.…”
mentioning
confidence: 99%
“…In some studies, a deficiency of plasma Lp-PLA2 was three times more common in children with severe bronchial asthma than in the general population, suggesting that Lp-PLA2 may play an important role in inflammatory and allergic responses (Stafforini et al 1999). Several other investigations have revealed that Lp-PLA2 mutations increase susceptibility to inflammatory and allergic diseases (Watson et al 1995;Tjoelker and Stafforini 2000).…”
Section: Discussionmentioning
confidence: 99%
“…About 80% of the Lp-PLA2 in plasma is bound to LDL via specific interaction between the C-terminus of apoB-100, the major constitutive protein of the LDL particle, and two domains of Lp-PLA2, one around tyrosine 205 and the other around tryptophan 115-leucine 116. The rest of the plasma Lp-PLA2 is bound to HDL and VLDL (Stafforini et al 1999;Kujiraoka et al 2003). The Lp-PLA2 enzyme is also known as platelet-activating factor (PAF) acetylhydrolase (PAF-AH), since one of its known functions is to deactivate PAF (Stafforini et al 1987a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Third, the lack of functional serum PAF acetylhydrolase, which catalyzes hydrolysis of PAF and short-chained sn-2 GPC, has been linked to an exacerbated asthma phenotype in the approximately 4% of the Japanese population with homozygous mutations. 130 Finally, PAF stimulates the production of the anti-inflammatory cytokine IL-10 in epidermal and other cell types. 124 Of significance, the PAF receptor appears to be able to bind to ligands other than PAF.…”
Section: Lipid-derived Mediatorsmentioning
confidence: 99%